Understanding Family Businesses in China: the Path, the Trend, and the Future - Valdivieso, José Félix (IE Fundation, 2020)
If, in a bid to unravel the knots of our recent history and identify the most important events of the fi rst two decades of the 21st century, we were to tele-transport ourselves into the living room of a historian in the year 3020—and in the absence of a further surprise by the goddess Clio—I believe our historian would undoubtedly highlight the impact of two things on our world. Firstly, the fall of the Twin Towers in 2001, and secondly, today’s economic/health crisis: both events can only be seen as creating an inescapable part of a new paradigm of globality, as yet to be defi ned.
Keywords: Family business; China